Different experiments for the production of charcoal with green coconut shells - Gama, Lucas; Ströher, Gylles Ricardo; Ströher, Gisely Luzia (Seven Editora, 2023)
OBJECTIVE: To produce charcoal from green coconut shells.  METHODS: The green coconut shells were collected from vendors in the city, sanitized, opened and placed outdoors to reduce humidity. 8 different experiments were carried out at varying temperatures (300 and 450ºC), time (1 and 2 h), and mass (35 and 100 g) to obtain the best product yield. The data were submitted to Tukey's new test, p